Enjoyment or Mastery? A Critical Evidence-Based Analysis of Dominant Outcomes in Gamified Learning - Tabassum, Nihal; Talha; Saeed, Ozal (The Indonesian Institute of Science and Technology Research, 2025)
This study investigates whether enjoyment or knowledge mastery plays a more dominant role in gamified learning environments. Using a semantic search across 138 million academic papers and systematic screening criteria, we identified empirical studies that measured both engagement-related and learning-related outcomes. Results reveal a conditional and sequential pattern rather than a single dominant effect. Enjoyment consistently drives initial engagement, supported by strong intrinsic motivation indicators and short-term affective gains. In contrast, mastery emerges more gradually and depends on the alignment of game elements with cognitive learning processes. Studies using superficial elements (e.g., points, badges) reported weaker learning effects, whereas meaningful game mechanics (challenges, feedback, narrative) fostered deeper understanding and retention. Comparative analyses show that enjoyment functions as a motivational catalyst, but mastery becomes dominant only when implementation fidelity is high and pedagogical objectives remain central. These findings highlight that effective gamification requires purposeful design that channels enjoyment into sustained learning pathways.